Escherichia coli is able to grow with negligible sodium ion extrusion activity at alkaline pH. - Ohyama, T (1992)
The Escherichia coli mutant NM81, which is deficient in the nhaA gene for the sodium/proton antiporter, still has a sodium ion extrusion activity because of a second antiporter encoded by nhaB (E. Padan, N. Maisler, D. Taglicht, R. Karpel, and S. Schuldiner, J. Biol. Chem. 264:20297-20302, 1989). By chance, we have found that E. coli pop6810 already contains a mutation affecting the sodium ion circulation, probably in or near nhaB, and that its delta nhaA mutant, designated RS1, has no sodium ion extrusion activity at alkaline pH. The growth of RS1 was inhibited completely by 0.1 M sodium, whereas growth inhibition of NM81 was observed only at sodium concentrations greater than 0.2 M. RS1 grew at a normal rate in an alkaline medium containing a low sodium concentration. Furthermore, RS1 grew with a negligible proton motive force in the alkaline medium containing carbonyl cyanide m-chlorophenylhydrazone. The transport activities for proline and serine were not impaired in RS1, suggesting that these transport systems could be driven by the proton motive force at alkaline pH. These findings led us to conclude that the operation of the sodium/proton antiporter is not essential for growth at alkaline pH but that the antiporter is required for maintaining a low internal sodium concentration when the growth medium contains a high concentration of these ions.